Physical activity in pregnancy: a qualitative study of the beliefs of overweight and obese pregnant women - Rankin Judith; McParlin Catherine; Robson Stephen C; Bush Judith; Weir Zoe; Bell Ruth (BMC, 2010)
Abstract Background Whilst there has been increasing research interest in interventions which promote physical activity during pregnancy few studies have yielded detailed insights into the views and experiences of overweight and obese pregnant women themselves. The qualitative study described in this paper aimed to: (i) explore the views and experiences of overweight and obese pregnant women; and (ii) inform interventions which could promote the adoption of physical activity during pregnancy. Methods The study was framed by a combined Subtle Realism and Theory of Planned Behaviour (TPB) approach. This enabled us to examine the hypothetical pathway between beliefs and physical activity intentions within the context of day to day life. The study sample for the qualitative study was chosen by stratified, purposive sampling from a previous study of physical activity measurements in pregnancy. Research participants for the current study were recruited on the basis of Body Mass Index (BMI) at booking and parity. Semi-structured, in-depth interviews were conducted with 14 overweight and obese pregnant women. Data analysis was undertaken using a Framework Approach and was informed by TPB. Results Healthy eating was often viewed as being of greater importance for the health of mother and baby than participation in physical activity. A commonly cited motivator for maintaining physical activity during pregnancy is an aid to reducing pregnancy-related weight gain. However, participants often described how they would wait until the postnatal period to try and lose weight. A wide range of barriers to physical activity during pregnancy were highlighted including both internal (physical and psychological) and external (work, family, time and environmental). The study participants also lacked access to consistent information, advice and support on the benefits of physical activity during pregnancy. Conclusions Interventions to encourage recommended levels of physical activity in pregnancy should be accompanied by accessible and consistent information about the positive effects for mother and baby. More research is required to examine how to overcome barriers to physical activity and to understand which interventions could be most effective for overweight/obese pregnant women. Midwives should be encouraged to do more to promote activity in pregnancy.